Phylogenetic analyses supporting Araiostegiella faberiana to be a distinct species from A. perdurans (Davalliaceae) - Dong, Shi-Yong; Huang, Jun-Kai (Phytotaxa, 2026)
The fern species Araiostegia faberiana has long been recognized as a distinct species in Chinese floras. However, it has recently proposed to be conspecific with A. perdurans. Upon examining herbarium specimens, we found that the type specimen’s morphology of A. faberiana (with opposite pinnules) conflicts with its established application to plants with catadromous pinnules, and that the type materials of A. perdurans comprise fronds of two morphological forms: catadromous-pinnuled and opposite-pinnuled. In this study we analyzed the plastid region atpB-accD to test whether phylogenetic divergence exists between these two morphological forms. Our analysis resolved specimens with catadromous pinnules as sister to those with opposite pinnules, supporting that A. faberiana is a distinct species from A. perdurans and A. hookeri. Therefore, the name A. faberiana should be conserved in nomenclature by designating a type specimen. The new combination Davallia faberiana is established for A. faberiana transferred to Davallia.